Epidemiology and Transmission Dynamics of Viral Encephalitides in West Africa - Olalekan Chris Akinsulie; Ridwan Olamilekan Adesola; Victor Ayodele Aliyu; Ifeoluwa Peace Oladapo; Abdulafees Hamzat (Infectious Disease Reports, 2023)
Encephalitis is an inflammation of the brain, often caused by an autoimmune reaction, or in most cases because of a direct viral, bacterial, or parasitic infection. Viral encephalitides (VE) presents a significant public health concern globally, especially in West Africa. There are more than five hundred known arthropod-borne viruses (arboviruses), with over a hundred of them identified to cause encephalitic diseases in humans and animals, giving rise to a tremendous burden of the diseases and socioeconomic strains in tropical and subtropical regions worldwide. Despite their importance, few effective preventive and control measures in the form of vaccines and therapies are available, and when they are, their use is limited. These limitations are largely hinged on the paucity of information about the molecular epidemiology and transmission patterns of VE in West Africa. Here, we reviewed the transmission dynamics, molecular epidemiology, and the ecological drivers of VE in West Africa. Collectively, timely and accurate interventions are essential for encephalitic viral disease control. Moreover, the integrated health system approach, combining surveillance, vaccination, vector control, and community engagement, could be effective in preventing viral encephalitis globally.